(untitled) (Scientific journal of the Fergana State University, 2024)
This study aims to investigate the special features and categories of public speaking, focusing on its emotional, persuasive, and interactive aspects. The researcher systematically reviewed the literature, analyzing about 50 studies published between 2000 and 2022. The findings suggest that public speaking is a complex and multifaceted phenomenon that involves emotional connection, persuasion, interactivity, and feedback. The study identifies six distinct categories of public speaking: informative, persuasive, entertaining, inspirational, demonstrative, and expository. The results highlight the importance of establishing emotional connections with the audience, using persuasive tactics, and incorporating interactive elements into presentations. This study contributes to our understanding of public speaking as a critical communication method, with implications for researchers, practitioners, and educators seeking to improve their public speaking skills.